Effective gene editing by high-fidelity base editor 2 in mouse zygotes. Issue 8 (5th June 2017) - Liang, Puping; Sun, Hongwei; Sun, Ying; Zhang, Xiya; Xie, Xiaowei; Zhang, Jinran; Zhang, Zhen; Chen, Yuxi; Ding, Chenhui; Xiong, Yuanyan; Ma, Wenbin; Liu, Dan; et al.
Abstract: Targeted point mutagenesis through homologous recombination has been widely used in genetic studies and holds considerable promise for repairing disease-causing mutations in patients. However, problems such as mosaicism and low mutagenesis efficiency continue to pose challenges to clinical application of such approaches. Recently, a base editor (BE) system built on cytidine (C) deaminase and CRISPR/Cas9 technology was developed as an alternative method for targeted point mutagenesis in plant, yeast, and human cells. Base editors convert C in the deamination window to thymidine (T) efficiently, however, it remains unclear whether targeted base editing in mouse embryos is feasible. In this report, we generated a modified high-fidelity version of base editor 2 (HF2-BE2), and investigated its base editing efficacy in mouse embryos. We found that HF2-BE2 could convert C to T efficiently, with up to 100% biallelic mutation efficiency in mouse embryos. Unlike BE3, HF2-BE2 could convert C to T on both the target and non-target strand, expanding the editing scope of base editors. Surprisingly, we found HF2-BE2 could also deaminate C that was proximal to the gRNA-binding region. Taken together, our work demonstrates the feasibility of generating point mutations in mouse by base editing, and underscores the need to carefully optimize base editing systems in order to eliminate proximal-site deamination.